(untitled) (JOYCED: Journal of Early Childhood Education, 2025)
This study aims to increase awareness and implementation of Clean and Healthy Lifestyle (PHBS) in early childhood through the implementation of Problem Solving-based learning model. This study uses Classroom Action Research (CAR) approach which is implemented in two cycles. The subjects of the study were 14 students of group B at TKS Muslimat NU XVIII Pamekasan. Data were collected through direct observation using daily child behavior assessment sheets related to PHBS, and analyzed descriptively-analytical. The results showed a significant increase in the implementation of PHBS. In cycle I, the average success of children in carrying out PHBS indicators was only 49.13%, with most children still in the category of Starting to Develop (MB). After improvements were made to learning strategies and approaches in cycle II, the average success increased to 80.56%, with most children showing behaviors Developing According to Expectations (BSH) and Developing Very Well (BSB). The indicators that experienced the most significant increase included the habit of washing hands with soap, brushing teeth regularly, and consuming vegetables and fruits every day. This study has limitations, especially in measuring behavioral changes consistently due to time constraints and the potential influence of the environment outside the school. However, the results of this study indicate that the Problem Solving learning model is effective in forming healthy living habits from an early age. This approach can be applied more widely in other early childhood education institutions as a preventive effort to build health awareness from an early age as a whole.